The Wikipedia news network: understanding collective response to current events through the internet’s encyclopaedia - Gildersleve, P (2021)
Wikipedia is the primary authoritative information resource on the web for billions of people, and perhaps the most important reference work in human history. Its modernised notion of the encyclopaedia is a widely accessible and rapidly updatable record for both historical knowledge and current events. The trove of available trace data from its users' browsing patterns also means that the site acts as an appealing, representative barometer for wider patterns of collective attention.